The Contribution of Popular Education in the Consolidation of Solidary Enterprises: A Case Study of COOPERTAN (Interdisciplinary Studies Journal, 2024)
This study examines the role of Popular Education in promoting the autonomy of waste pickers from COOPERTAN, a cooperative of recyclable materials in Tangará da Serra, MT. Popular Education, based on the principles of participation and emancipation, is a fundamental approach to strengthen Solidary Economic Enterprises (SEE), such as COOPERTAN, facing bureaucratic challenges and promoting self-management. The research focuses on accounting as an essential tool for the consolidation of these enterprises, recognizing the importance of transparency and financial planning for effective management. Through a qualitative methodological approach, using Iramuteq software for data analysis, the study highlights the intersection between Popular Education, Solidarity Economy, and cooperativism. The analyses reveal the challenges and opportunities found in COOPERTAN's accounting training process, emphasizing the need for inclusive educational methodologies adapted to the needs of SEE. In summary, the study highlights the importance of Popular Education as a transformative tool to empower waste pickers and strengthen the autonomy and effectiveness of solidary enterprises.
Keywords: Popular Education; Self-Management Cooperativism; Accounting